Comprehensive Rehabilitation Therapy for A Child with Reducing Body Myopathy - Xinhong WU; Fan WU; Yun ZHANG; Taibiao LI; Tiebin YAN (康复学报)
Objective:To investigate the characteristics and rehabilitation therapy of a case with reducing body myopathy (RBM).Methods:A case of a child with limb weakness due to RBM was admitted, and the clinical features, laboratory tests results, imaging findings, muscle pathology and genetic testing results of the child were analyzed. After the child received comprehensive rehabilitation therapy, histransfer ability, muscle strength, muscle tone, range of motion and gross motor function measure (GMFM) score were evaluated before and after the treatment.Results:FHL1 gene and heterozygous mutation of c. C369G gene were detected in this case. His manifestations were consistent with what RBM presents. After the comprehensive rehabilitation treatment, the muscle strength, GMFM-88, Berg balance scores were increased significantly.Conclusion:Comprehensive rehabilitation training can maintain the body muscle strength and balance capability, improve motor function and transfer ability, and may delay the progress of the disease.